Medieval Naples : an Architectural & Urban History, 400-1400 - Bruzelius, Caroline Astrid; Tronzo, William (Documentary history of Naples., 2011)
Two leading American experts on the subject offer the first comprehensive English-language review of Naples' architecture and urban development from late antiquity to the high and late Middle Ages. William Tronzo treats the early Middle Ages, from the end of the western Roman Empire to the end of the Duchy, or from about 400 to about 1139. Caroline Bruzelius then picks up the narrative and analysis from the twelfth century to the end of the Angevin period, or about 1400. Clearly and concisely written, it is an ideal introductory survey for the scholar, student and general reader to medieval Na.